Pancasila education Pancasila as the Foundation of Ethics - Salsabila, Tasya (Indonesian Journal of Pancasila and Global Constitutionalism, 2023)
This journal aims to critically analyze the concept of Pancasila as an ethical foundation in the Indonesian social, political and cultural context. Through a literature review, it explores the history and development of Pancasila, and examines its relevance and implementation in modern society. It also outlines Pancasila's contribution to the development of ethics and social norms, as well as the challenges that may be faced in applying these principles. The results of this analysis provide deep insight into the role of Pancasila as an ethical guide in building a just and equitable society in Indonesia.